Chitosan-coated nanoemulsion for intranasal administration increases temozolomide mucosal permeation, cellular uptake, and In vitro cytotoxicity in glioblastoma multiforme cells - Duarte, Jonatas Lobato [UNESP]; Di Filippo, Leonardo Delello [UNESP]; Azevedo Vilella, Kelle Jarcy [UNESP]; Paes Dutra, Jessyca Aparecida [UNESP]; Ribeiro, Diego Messalle [UNESP]; Freitas da Silva, Mônica; Ivo de Medeiros, Alexandra [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2024)
Glioblastoma multiforme (GBM) is the most prevalent and aggressive type of brain cancer in adults. Temozolomide (TMZ) is the chemotherapeutic agent used to treat primary central nervous system tumors. However, TMZ's clinical effectiveness faces several challenges due to its physical-chemical properties and biological features of GBM, such as the blood-brain barrier (BBB). Mucoadhesive nanosystems such as those coated with chitosan represent a promising alternative for optimizing the delivery of therapeutic agents to the central nervous system, as they possess ideal characteristics that enhance their interaction with the intranasal mucosa. We aimed to develop a chitosan-coated nanoemulsion containing temozolomide (CS-NE-TMZ) for nose-to-brain delivery and characterize its physical-chemical and in vitro biological properties. CS-NE-TMZ were obtained by emulsification followed by sonication. The optimized CS-NE-TMZ presented droplet size of 123,4 ± 2,3 nm, polydispersity index of 0.273 ± 0.028, zeta potential of +21,5 ± 0,81 mV, entrapment efficiency of 100 ± 1,91 % and drug loading of 2 ± 0,007 %. An in vitro release study of CS-NE-TMZ showed sustained release for up to 24 h following the Korsmeyer-Peppas model with Fickian diffusion. CS-NE-TMZ demonstrated significantly enhanced ex vivo mucosal permeation, compared to free TMZ, and showed enhanced in vitro cellular uptake, selectively increasing cytotoxicity in U-87MG glioma cells but not in healthy L929 fibroblasts, reinforcing the potential of mucoadhesive nanoemulsions as effective intranasal drug delivery systems for future brain cancer therapies.
Keywords: Brain cancer; Chitosan; Drug delivery; Lipid nanocarrier; Nose-to-brain